Peningkatan Keterampilan Membaca Permulaan Menggunakan Metode SAS Berbantu Media Gambar di Kelas II SDN 127/II Sungai Arang - Afrianti, Viranika; Aprizan, Aprizan; Abdullah, Abdullah (CV. Master Literasi Indonesia, 2025)
Classroom Action Research on second-grade students at SDN 127/I1 Sungai Arang is based on initial observations that indicate a low result in early reading learning. The average score for students in early reading about their enthusiasm for going to school is 60, while the learning achievement criteria (KKTP) set by the school is 70. This indicates that the reading results of the students are still low. Therefore, the learning method that can improve students' learning outcomes is the Analytical Synthetic Structural Method. This study aims to explain how the Analytical Synthetic Structural Method, with the help of picture media, improves early reading skills in each cycle. Classroom Action Research is the research methodology employed. “Planning, action implementation, observation, and reflection comprised each of the three cycles of the research”. The subjects of this research were 18 students of grade II of SDN 127/II Sungai Arang. Data collection used in this research was the teacher observation sheet, student observation sheet, and reading test result instrument. “The results obtained from this research include: the application of learning using synthetic analytical structural methods assisted by image media can improve the Indonesian language learning process of class II students at SDN 127/II Sungai Arang”. This can be seen from the teaching process of educators in cycle 1, meeting 1, 55.71%, then at meeting 2 68.57% and in cycle 2, meeting 1, 84.28% and at meeting 2, 95.71%. This is how students' observations also experience improvement in each meeting. Meanwhile, the reading ability test results in cycle 1 were 50% and cycle 2 were 77.78% in the good category. “It can be concluded that the use of the Synthetic Analytical Structural Method with Image Media can improve beginner reading skills in class II at SDN 127/II Sungai Arang